2013
DOI: 10.1177/1524500413515448
|View full text |Cite
|
Sign up to set email alerts
|

Boaters’ Perceptions of a Mobile App for a Marine Conservation Social Marketing Campaign

Abstract: This case study explored recreational boaters' perceptions of a mobile app being developed in the context of a campaign to promote environmental responsibility in a U.S. Florida lagoon. Transcripts from six focus groups conducted with a target population of boaters to guide the conservation campaign were analyzed to identify and understand the barriers and benefits of the app that may influence its adoption with the desired behavior of better navigating the lagoon. Extant literature on social marketing and ado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Though focusing on a very different topic, the results from the mobile giving study are similar to one that examines the adoption of a mobile phone application as part of a marine conservation social marketing campaign. Bowerman and DeLorme (2014) found that the perceptions an individual had about the efficacy of mobile phone applications and the social issue at hand had significant influence as to whether one would download and use the application. This parallels the finding that individual behaviors are driven by information seeking and information processing (Weberling et al, 2012).…”
Section: Jsocm 43mentioning
confidence: 99%
“…Though focusing on a very different topic, the results from the mobile giving study are similar to one that examines the adoption of a mobile phone application as part of a marine conservation social marketing campaign. Bowerman and DeLorme (2014) found that the perceptions an individual had about the efficacy of mobile phone applications and the social issue at hand had significant influence as to whether one would download and use the application. This parallels the finding that individual behaviors are driven by information seeking and information processing (Weberling et al, 2012).…”
Section: Jsocm 43mentioning
confidence: 99%
“…There is as yet very little information, either through programme monitoring and evaluation, or in the scholarly literature on the value and impact 11 https://www.youtube.com/watch?v=ENpt585-0Zo&feature=youtu.be 12 http://www.pc.gc.ca/eng/amnc-nmca/qc/saguenay/index.aspx of digital technology to influence people's awareness, attitudes and behaviour, particularly in regard to environmental social marketing. An improved understanding of mobile technologies with regard to environmental social marketing, and specific case-by-case understanding by MPA authorities and conservation practitioners of the audiences they are attempting to communicate with are required (Bowerman and DeLorme, 2014).…”
Section: Integratementioning
confidence: 99%
“…In order to achieve positive action, it is necessary for MPA authorities and ocean conservation professionals to understand the barriers to making an impact on people's awareness, attitudes and behaviour, and what benefits they would derive from increased awareness, a positive attitude to MPAs and marine conservation, and taking action to support it. An understanding of the barriers and benefits from the perspective of target audiences can help determine and refine messages, as well as implement tools that can highlight benefits while downplaying or minimizing barriers (Bowerman and DeLorme, ). Furthermore, tailoring messages that speak to the intended audience and stand out in a crowded marketplace of ideas in today's overloaded media and advertising environment is a challenge all organizations face, but must be addressed head on.…”
Section: Make It Relevantmentioning
confidence: 99%
“…Now armed with unlimited access to digital technologies, citizens can now "pull" the information when, where, from whom they want and at a time that is convenient to them (Hastings and Domegan, 2018). They no longer want content to be imposed on them (Bowerman and DeLorme, 2014). Power has now shifted to citizens, who now have a desire to be active participants in content and value co-creation and exchanges (Lefebvre, 2009;Ledford, 2012).…”
mentioning
confidence: 99%